若 (f(n)=sum_{i=0}^ninom{n}{i}g(i)),则 (g(n)=sum_{i=0}^n(-1)^{n-i}inom{n}{i}f(i)) 。
证明:
[g(n)=sum_{i=0}^n(-1)^{n-i}inom{n}{i}f(i)\
=sum_{i=0}^n(-1)^{n-i}inom{n}{i}sum_{j=0}^iinom{i}{j}g(j)\
=sum_{i=0}^n(-1)^{n-i}sum_{j=0}^iinom{n}{i}inom{i}{j}g(j)\
]
由三项式版恒等式
[inom{r}{m}inom{m}{k}=inom{r}{k}inom{r-k}{m-k} (m,kin Z)
]
得
[g(n)=sum_{i=0}^n(-1)^{n-i}sum_{j=0}^iinom{n}{i}inom{i}{j}g(j)\
=sum_{i=0}^n(-1)^{n-i}sum_{j=0}^iinom{n}{j}inom{n-j}{i-j}g(j)\
=sum_{i=0}^nsum_{j=0}^i(-1)^{n-i}inom{n}{j}inom{n-j}{i-j}g(j)\
=sum_{j=0}^ng(j)inom{n}{j}sum_{i=j}^n(-1)^{n-i}inom{n-j}{i-j}\
=sum_{j=0}^ng(j)inom{n}{j}sum_{i=0}^{n-j}(-1)^{n-j-i}inom{n-j}{i}\
]
而又有
[sum_{i=0}^n(-1)^{i}inom{n}{i}=[n=0]
]
所以
[g(n)=sum_{j=0}^ng(j)inom{n}{j}sum_{i=0}^{n-j}(-1)^{n-j-i}inom{n-j}{i}\
=g(n)inom{n}{n}\
=g(n)
]
证毕。